Global mapping of fact-checking on Instagram. Content formats and their effect on engagement - García-Marín, David (Estudios sobre el Mensaje Periodístico, 2024)
This paper presents an exhaustive study on the use of Instagram by fact-checking journalism at a global level. Specifically, it analyzes the use of the formats allowed by this platform (photo, album, and video) and their effect on two key engagement indicators: likes and comments. Descriptive and inferential statistics (multiple linear regressions) were used to analyze all the posts of the fact-checkers belonging to IFCN published up to October 2023 (n=95631; 80 fact-checkers from 49 countries). There are significant differences in the use of the formats by world regions. Globally, the format has a greater effect on the number of likes than on comments. Latin American and Asian fact-checkers make better use of the platform, since they use the formats that are most effective in driving both likes and comments. The most significant differences between the use of formats and engagement are to be found in Europe: the usage of the single photograph is the most common, even though it is the format that receives the least number of likes and comments. Although in general terms the use of the album format significantly boosts both indicators, there are significant deviations in engagement between the different regions, which demonstrates its contextual nature and the difficulty of establishing general guidelines to enhance it.